One day in the desert - George, Jean Craighead; Brenner, Fred (New York : HarperCollins Pub, 1983)
Explains how the animal and human inhabitants of the Sonoran Desert of Arizona, including a mountain lion, a roadrunner, a coyote, a tortoise, and members of the Papago Indian tribe, adapt to and survive the desert's merciless heat.
Includes index.
Bibliography: p. 45.
Keywords: Desert ecology -- Sonoran Desert; Desert ecology; Heat; Tohono O'odham Indians; Indians of North America -- Arizona; Ecology